2022
DOI: 10.3928/1081597x-20211209-01
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Refractive Outcomes Following SMILE to Correct Myopia Performed by Surgeons in Training

Abstract: PURPOSE: To assess visual outcomes and complications following small incision lenticule extraction (SMILE) performed by cornea fellows under the supervision of experienced surgeons. METHODS: This retrospective, noncomparative case series was designed to assess outcomes following SMILE procedures performed at a large surgical center by cornea fellows between May 1, 2012 and March 30, 2015. Preoperative and postoperative uncorrected distance visual acuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Also, Ramirez-Miranda et al’s study surveilled 160 eyes undergoing SMILE for postoperative complications and found that the most common postoperative complication was epithelial defect, representing 11.2% incidence. Once again, the authors attributed this to surgical experience as these defects occurred with surgeons that were acclimating to the technique required to dissect and extract a lenticule, noting that after 4-6 SMILE surgeries, the defect disappeared [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Ramirez-Miranda et al’s study surveilled 160 eyes undergoing SMILE for postoperative complications and found that the most common postoperative complication was epithelial defect, representing 11.2% incidence. Once again, the authors attributed this to surgical experience as these defects occurred with surgeons that were acclimating to the technique required to dissect and extract a lenticule, noting that after 4-6 SMILE surgeries, the defect disappeared [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Epithelial defects occur less frequently in SMILE compared to LASIK [24][25][26][27]. Visual prognosis following treatment is generally favorable [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Smilementioning
confidence: 99%
See 1 more Smart Citation
“…Incidence for epithelial defects and abrasions after SMILE range from 0.17% 6 to 7.4%. 14 In another study, Ramirez-Miranda et al reported an incidence of 11.25% of epithelial defects after SMILE; however, the surgeons performing SMILE in this study were recently introduced to the SMILE surgical technique. 15 This technique included the use of a spatula to remove the lenticule; however, it is noted that forceps can also be used for this process while performing the surgery.…”
Section: Discussionmentioning
confidence: 64%
“…The procedure involves femtosecond laser creation of a small lenticule of anterior stroma, which is subsequently removed through a 2 to 3 millimeter tunnel incision. Ramirez-Miranda et al published the first reported outcomes of SMILE performed by trainees, reviewing cases performed by 9 fellows [10 ▪▪ ]. They found that 97% of patients had 20/40 vision or better at 6 months postoperatively; however only 61% of patients had 20/20 vision or better.…”
Section: Outcomes Of Trainee Performed Refractive Surgerymentioning
confidence: 99%